2001
DOI: 10.2337/diacare.24.10.1810
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Microcirculatory Impairment in Diabetic Patients With Foot at Risk

Abstract: OBJECTIVE -To assess microcirculatory impairment and alterations of the skin oxygen supply in diabetic patients with foot at risk.RESEARCH DESIGN AND METHODS -This study evaluated skin blood flow in 21 type 2 diabetic patients with a foot at risk (defined as a foot with neuropathy but without ulceration or previous ulcerations), 20 type 2 diabetic patients without foot lesions or neuropathy, and 21 normal subjects as a control group. The skin blood flow was determined by measuring the transcutaneous oxygen pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 20 publications
3
66
0
2
Order By: Relevance
“…Atherosclerosis of large and medium-sized arteries and microangiopathy affecting small vessels cause ischemic ulcers. 23 Nevertheless, other patients develop neurotrophic ulcerations in the absence of ischemia. Both ischemic and neurotrophic ulcerations can be complicated by localized infection and heal with considerable difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis of large and medium-sized arteries and microangiopathy affecting small vessels cause ischemic ulcers. 23 Nevertheless, other patients develop neurotrophic ulcerations in the absence of ischemia. Both ischemic and neurotrophic ulcerations can be complicated by localized infection and heal with considerable difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Altered wound repair is present in animal models of diabetes such as non-obese diabetic mice (NOD), db/db mice [15][16][17][18][19][20][21][22][23][24][25][26] and mice in which the diabetes was induced by treatment with streptozotocin. NOD mice develop a form of diabetes similar to human type-I insulin-dependent diabetes, also known as type 1 diabetes, that is an organspecific autoimmune disease resulting from the destruction of insulin-producing pancreatic ␤ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of lower-limb amputation is 15 times higher in diabetic patients than nondiabetics, and more than 50 percent of diabetic patients with an amputation need subsequent amputation of the contralateral limb within 5 yr of the loss of the first leg [3]. Diabetic wounds are chronic open sores that are hard to heal because of poor blood circulation at the wound sites [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been suggested that the impaired perfusion at the tissue level observed as a complication of diabetes mellitus is primarily due to the reduced erythrocyte deformability (39,40). Besides, metabolic changes and tissue perfusion due to cardiovascular problems may lead to inadequate recovery in plasma viscosity (41).…”
Section: Resultsmentioning
confidence: 99%